Parental career value, salary and gender as correlates of students' attitude towards teaching profession (2012)
This study investigated the topic student's attitude towards teaching profession and the role parental career value, salary and gender plays on their attitude. Six hundred Senior Secondary IIstudents and their parents were selected through multi stage sampling technique. Three instruments were used for data collection: Students Teaching Profession Attitude Questionnaire ( r=O.72), Salary and Incentive Scale (r = 0.89) and Parental career value scale (r = 0.51) validated using Cronbach Alpha Reliability Analysis. The data collected were analysed using descriptive statistics and multiple regression. Students' attitude towards teaching profession based on this study was found to be negative. Also the study revealed that parental career value, salary and gender jointly predict students attitude towards teaching profession (df=3,471, F=88.267, p<0.05). Subsequently when the relative contributions of the independent variables were investigated, only salary was the influential variable (β=.600, t=16.262, p<0.05), while parental career value and gender were not significantly influential. It was recommended based on the findings that government and other stakeholders' should remunerate teachers with better salary to encourage young ones to have positive attitude to the profession and go into it later in life. Practicing teachers are equally advised to conduct themselves in manner befitting their professional ethics and maintain highest standard so as to portray a good image of the profession both to the students and the entire society.